Spartan - Manfredi, Valerio Massimo (Pan Books, 2014)
Herodotus tells us that not all of the three hundred Spartan warriors died at the hands of Xerxes, King of the Persians, in the battle of the Thermopylae: two were saved bringing a life-saving message back to the city... Valerio Massimo Manfredi's Spartan is the saga of a Spartan family, torn apart by a cruel law that forces them to abandon one of their two sons - born lame - to the elements. The elder son, Brithos, is raised in the caste of the warriors, while the other, Talos, is spared a cruel death and is raised by a Helot shepherd, among the peasants. They live out their story in a world dominated by the clash between the Persian empire and the city-states of Greece - a ferocious, relentless conflict - until the voice of their blood and of human solidarity unites them in a thrilling, singular enterprise.